Aiueo Therapy in Improving Speech Ability in Aphasia with Cerebral Infarction at Chuzan Hospital Okinawa Japan - Muzakiyah, Luluk Latifatul; Iqmh, Muhammad Khabib Burhanuddin (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Cerebral infarction (ischemic stroke) is a condition when blood flow to the brain is obstructed, causing damage to brain tissue. Cerebral infarction is one of the most common cerebrovascular diseases and can result in severe residual functional disability that permanently affects the patient's activities of daily living and quality of life. One of them is aphasia or impaired language function. Elderly people with aphasia will be given AIUEO therapy which aims to improve speech so that spoken articulation is clear. This research aims to determine the effectiveness of applying AIUEO therapy in improving the speaking ability of aphasia patients. The type of research used in this case study is descriptive. AIUEO therapy for Mrs. E can improve verbal communication because the patient is able to express his wishes directly and does not use writing. The patient's speech can also sometimes be heard quite clearly. Evaluation of Mrs. E for 3 days shows an increase in the patient's communication after being given AIUEO therapy. There is an effect of AIUEO therapy on improving speaking ability.